2015
DOI: 10.1111/jgs.13635
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Gallstone Ileus with Giant Stone: A Case Report and Literature Review

Abstract: role. This small, single-center study suggests that hyponatremia may not be optimally documented in discharge summaries and might predispose people to hospital readmission. Efforts to improve recognition and treatment of hyponatremia in the outpatient setting may help reduce falls and fractures in older persons with this risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…A retrospective study showed EF and BR were independently associated with higher mortality than ES, on multivariate analysis . And enterotomy with stone extraction remains the most popular surgical option; however, consistent with our case, there are some reports of spontaneous resolution of gallstone ileus, with patients passing the stones through the rectum, although there is no clear indicator of whether spontaneous evacuation of gallstones can be expected. Recurrence of gallstone ileus occurs in 5% of cases, with 85% within 6 months of the initial episode …”
Section: Discussionsupporting
confidence: 72%
“…A retrospective study showed EF and BR were independently associated with higher mortality than ES, on multivariate analysis . And enterotomy with stone extraction remains the most popular surgical option; however, consistent with our case, there are some reports of spontaneous resolution of gallstone ileus, with patients passing the stones through the rectum, although there is no clear indicator of whether spontaneous evacuation of gallstones can be expected. Recurrence of gallstone ileus occurs in 5% of cases, with 85% within 6 months of the initial episode …”
Section: Discussionsupporting
confidence: 72%
“…Another possible explanation is that conservative treatment may be chosen more frequently than before. Indeed, recent reports suggest the majority of cases now undergo spontaneous stone evacuation or endoscopic treatment [5][6][7][8][9] . The precise diagnosis of gallstone ileus using modern diagnostic radiology might have accelerated this trend.…”
Section: Discussionmentioning
confidence: 99%
“…The precise diagnosis of gallstone ileus using modern diagnostic radiology might have accelerated this trend. Besides, conservative management to avoid surgery is preferred, especially in older patients who often have severe comorbidities 8) . In our patient, gallstone ileus was accompanied by severe dehydration, acute renal failure, and enteritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations